IMPACTS OF TOURISM ON COMMUNITIES AROUND THE AREA OF PHU TOEI NATIONAL PARK SUPHANBURI PROVINCE - Likitsarun, Nuchpravee (Journal of Sports Science and Health, 2019)
Purpose This research aimed to study the impact of tourism on the communities around Phu Toei National Park, Suphanburi Province Research Methods This is a qauntitative research. The questionnaire survey was based on the affect on tourist with Economy, Society, Enviorment and Culture in the area of around Phu Toei National Park, Suphanburi Province. The data collection was from 400 local people. Statistics used in data analysis are number, percentage, and mean. Results Most of questionnaire respondents are females aged between 20-30 years old, single, graduated from high school or equivalence, working as farmer, and having a monthly income of 10,000-20,000 Baht per month. Findings were found that the impact of tourism in overall aspect was in high level. There was 1) The economic affected the tourist attraction in high level. The factor that mostly affected the economic was the income distribution to local people. 2) The society affected the tourist attraction in high level. The factor that mostly affected the society is the safety of their life and values of tourist and local people in the area of Phu Toei National Park. 3) The environment affected the tourist attraction in high level. The factor that mostly affected the environment was the nature deteriorating. 4) The culture affected the tourist attraction in moderate level. The factor that mostly affected the culture is the traditions and culture exchange between local people and tourist. Conclusion The impact of tourism on the communities around the National Park Suphanburi Province, has the most positive impact on tourism is the distribution of tourism income to the people in the area. The negative impact of tourism is that the people in the community have different income